Application of Android-Based Interactive Learning Media in Clean Water Pipe Installation System Teaching Material (Journal of Vocational and Career Education, 2022)
The widespread use of smartphones among students has not been fully utilized to support the learning process. This study aims to develop interactive Android-based learning media that is attractive to eleventh grade students of KGSP to improve basic competence in analyzing clean water pipe installation systems. The research method used in the development of interactive learning media is research and development (RD). The development model used is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). It is design model that is more generic and serves as a guide in developing tools and infrastructure for effective training programs. Data analysis is used to determine the level of feasibility, the level of practicality, and to determine the effectiveness of Android learning media to improve basic competence in analyzing clean water pipe installation systems. Based on the obtained data, it can be concluded that the criteria of the media are very feasible, very practical, effective, and significant for increasing the basic competence of analyzing clean water pipe installation systems for SMK students in the KGSP expertise program.